Comparison of Erythrocyte Sedimentation Rate by Vision Principle and Westergren Method - Aayza Mujahid, Jawad Zaffar Choudry, Hamid Iqbal, Syeda Bint-E-Zahra, Saadia Latif, Zahra Habib (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Erythrocyte sedimentation rate is a common test used as an assessment tool for inflammation since many years. Aim: To compare erythrocyte sedimentation rate by automated ESR analyzer working on vision principle against conventional manual Westergren method. Study design: Cross sectional study. Methodology: A total number of 120 samples were taken from routine hospital patients whom ESR was requested through non-probability consecutive sampling following ethical approval. Samples were subjected to ESR estimation by manual Westergren and automated methods. Data was analyzed by SPSS version 22. Independent sample t-test used to compare erythrocyte sedimentation rate by automated ESR analyzer working on vision principle against conventional manual Westergren method with p-value ≤0.05 as significant. Pearson correlation was also applied. Results: Mean ± SD for Manual Westergren method was 39.37±25.486 and Automated Vision principle was 25.83±21.015. Levene’s Test for Equality of Variances have p-values for ESR in patients with Manual Westergren method & Automated Vision principle was 0.018 with F-value 5.670. There was a non-linear relationship between the two methods (P value < 0.01). Practical Implication: This study helped in exploring reliability of different ESR estimation methods as ESR results have notable impact on patient diagnosis and follow-up. With increasing demands and burden of patients in labs, new reliable and quick techniques for ESR determination are need of hour. Conclusion: It was concluded that automated methods showed good correlation to manual Westergren method thus are reliable for ESR estimation. However, manual Westergren remained gold standard procedure for ESR estimation. Keywords: Erythrocyte Sedimentation Rate, Reliability, Westergren Method and Automated Method.